“Novinha(s) do Acre”:: a discussion on gender and ethics in journalistic coverage on the website ac24horas (Intercom - Brazilian Journal of Communication Sciences, 2026)
This article analyzes the journalistic ethics of the website ac24horas based on its coverage of gender issues involving underage girls. The corpus consists of eight news articles that include the term "novinha" in their titles, collected between 2016 and 2021. In the context of funk, the use of the term "novinha" emerged in Brazilian funk as a way to objectify and sexualize the body of a young woman. When journalists appropriate this term and use it in news, we see that this meaning persists. All articles published on ac24horas that include the word "novinha(s)" in the title were selected for analysis. The bibliographic references include studies by Simone de Beauvoir (2019), Rogério Christofoletti (2008, 2016), and Aldo Antônio Schmitz (2011), among other authors.
Keywords: gender; journalistic ethics; journalism; women.